Serum Neurofilament Light and GFAP Are Associated With Disease Severity in Inflammatory Disorders With Aquaporin-4 or Myelin Oligodendrocyte Glycoprotein Antibodies - Chang, Xuechun; Huang, Wenjuan; Wang, Liang; ZhangBao, Jingzi; Zhou, Lei; Lu, Chuanzhen; Wang, Min; Yu, Jian; Li, Haiqing; Li, Yuxin; Zhao, Chongbo; Lu, Jiahong; et al. (Frontiers in Immunology, 2021)
Objective To evaluate the potential of serum neurofilament light (sNfL) and serum glial fibrillary acidic protein (sGFAP) as disease biomarkers in neuromyelitis optica spectrum disorder (NMOSD) with aquaporin-4 antibody (AQP4-ab) or myelin oligodendrocyte glycoprotein-antibody-associated disease (MOGAD). Methods Patients with AQP4-ab-positive NMOSD (n = 51), MOGAD (n = 42), and relapsing-remitting multiple sclerosis (RRMS) (n = 31 for sNfL and n = 22 for sGFAP testing), as well as healthy controls (HCs) (n = 28), were enrolled prospectively. We assessed sNfL and sGFAP levels using ultrasensitive single-molecule assays. Correlations of sNfL and sGFAP levels with clinical parameters were further examined in AQP4-ab-positive NMOSD and MOGAD patients. Results sNfL levels were significantly higher in patients with AQP4-ab-positive NMOSD (median 17.6 pg/mL), MOGAD (27.2 pg/mL), and RRMS (24.5 pg/mL) than in HCs (7.4 pg/mL, all p < 0.001). sGFAP levels were remarkably increased in patients with AQP4-ab-positive NMOSD (274.1 pg/mL) and MOGAD (136.7 pg/mL) than in HCs (61.4 pg/mL, both p < 0.001). Besides, sGFAP levels were also significantly higher in patients with AQP4-ab-positive NMOSD compared to those in RRMS patients (66.5 pg/mL, p < 0.001). The sGFAP/sNfL ratio exhibited good discrimination among the three disease groups. sNfL levels increased during relapse in patients with MOGAD (p = 0.049) and RRMS (p < 0.001), while sGFAP levels increased during relapse in all three of the disease groups (all p < 0.05). Both sNfL and sGFAP concentrations correlated positively with Expanded Disability Status Scale scores in AQP4-ab-positive NMOSD (β = 1.88, p = 0.018 and β = 2.04, p = 0.032) and MOGAD patients (β = 1.98, p = 0.013 and β = 1.52, p = 0.008). Conclusion sNfL and sGFAP levels are associated with disease severity in AQP4-ab-positive NMOSD and MOGAD patients, and the sGFAP/sNfL ratio may reflect distinct disease pathogenesis.